2(n+2)=5n-2

Simple and best practice solution for 2(n+2)=5n-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(n+2)=5n-2 equation:


Simplifying
2(n + 2) = 5n + -2

Reorder the terms:
2(2 + n) = 5n + -2
(2 * 2 + n * 2) = 5n + -2
(4 + 2n) = 5n + -2

Reorder the terms:
4 + 2n = -2 + 5n

Solving
4 + 2n = -2 + 5n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-5n' to each side of the equation.
4 + 2n + -5n = -2 + 5n + -5n

Combine like terms: 2n + -5n = -3n
4 + -3n = -2 + 5n + -5n

Combine like terms: 5n + -5n = 0
4 + -3n = -2 + 0
4 + -3n = -2

Add '-4' to each side of the equation.
4 + -4 + -3n = -2 + -4

Combine like terms: 4 + -4 = 0
0 + -3n = -2 + -4
-3n = -2 + -4

Combine like terms: -2 + -4 = -6
-3n = -6

Divide each side by '-3'.
n = 2

Simplifying
n = 2

See similar equations:

| 4/5-5/8 | | (x+40)/2=64 | | N+2.6=4 | | -5(x+7)-43=8-41 | | 58+4x+2=10 | | 71-2=3x+16 | | 1+2x=7(x+1)-6(x-3) | | w/14-9/10 | | F(x)=x^51-7x^2+6 | | -6x+5+4x=-3x+10 | | 8n+6=5n+18 | | 65-13x=12x | | 7h/10+1/2=h/2-7/5 | | 9x+3=9(x+1) | | -(4-m)=-(5m+4) | | 8/3x+5=10 | | x-3/7=1-x/3 | | -6x-44(x+2)=-7(7x+5) | | -6/7r=-18 | | -1/2(11) | | 2/(x-9)^3=0 | | -7/20=-1/8x | | 3(x+3)=5x+3-2x+6 | | p/7=9/14 | | f(x)=-3(x+1)+3 | | 5x+6=3x+40 | | (a2+10a+21)/(a+3) | | 9=-q/6 | | -10n+9=-9n-10 | | 102-(5x+13)=5(x+9)+x | | 42=-2 | | 7/20=c+2/5 |

Equations solver categories